2001
DOI: 10.1042/0264-6021:3530299
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of bone marrow-derived macrophages to apoptosis is associated with the expression of X-linked inhibitor of apoptosis protein in primary cultures of bone marrow cells

Abstract: In this study we investigated the underlying mechanisms that confer resistance on mature macrophages with the use of macrophage colony-stimulating factor (M-CSF)-induced bone marrow-derived macrophages (BMDM). In the presence of M-CSF, immature precursor cells were induced to undergo proliferation and differentiation into mature macrophages in vitro with cell morphology similar to that of tissue macrophages by day 7-10. Immunoblot analyses showed that bone marrow precursors express appreciable levels of caspas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 40 publications
1
31
0
Order By: Relevance
“…We attempted to induce apoptosis using various activators of the extrinsic pathway of apoptosis (e.g., TNF-a, FasL, TRAIL), but we found that these agents did not induce apoptosis in BMDMs, even when cultured in the absence or presence of serum and LCM (not shown). These results are consistent with earlier studies that report significant resistance to apoptosis in mature macrophages subjected to growth factor withdrawal or addition of activators of the extrinsic pathway of cell death (21)(22)(23). Because macrophages are known to be susceptible to apoptosis induced by ER stress (24-27), we determined whether expression of BCAP influenced survival after addition of thapsigargin, a sarcoplasmic/endoplasmic reticulum calcium ATPase inhibitor that activates ER stress and the intrinsic pathway of apoptosis (28).…”
Section: Bcap Is Required For Maximal Protection Against Apoptosis Insupporting
confidence: 80%
“…We attempted to induce apoptosis using various activators of the extrinsic pathway of apoptosis (e.g., TNF-a, FasL, TRAIL), but we found that these agents did not induce apoptosis in BMDMs, even when cultured in the absence or presence of serum and LCM (not shown). These results are consistent with earlier studies that report significant resistance to apoptosis in mature macrophages subjected to growth factor withdrawal or addition of activators of the extrinsic pathway of cell death (21)(22)(23). Because macrophages are known to be susceptible to apoptosis induced by ER stress (24-27), we determined whether expression of BCAP influenced survival after addition of thapsigargin, a sarcoplasmic/endoplasmic reticulum calcium ATPase inhibitor that activates ER stress and the intrinsic pathway of apoptosis (28).…”
Section: Bcap Is Required For Maximal Protection Against Apoptosis Insupporting
confidence: 80%
“…Ratio = (Nuclear intensity -background intensity) ÷ (Cytoplasmic intensity -background intensity) .7 seeded into 6 well plates were cultured in DMEM before being activated for 1 h, with or without isoflavone pretreatment, as described above. Nuclear extraction and the EMSA were performed as described by Lin et al (2001) using the NF-kB consensus oligonucleotide 5'-AGTTG AGGGG ACTTT CCCAG GC-3'. In preliminary experiments, supershift polyclonal antibodies for p65 and p50 were incubated with activated cell nuclear extracts.…”
Section: Image Analysis Image Analysis Image Analysis Image Analysis mentioning
confidence: 99%
“…Murine BM-MØ were generated from the BM cells of the tibia and femur of C57Bl/6 donor mice by a modification of previously described protocols (Lin et al, 2001;Weischenfeldt and Porse, 2008). BM cells were harvested and cultured in R-10 medium containing 10 ng/ml of recombinant murine colony-stimulating factor (rmCSF-1; Immunotools, Friesoythe, Germany) in T-75 cell culture flasks.…”
Section: Generation Of Bm-mømentioning
confidence: 99%